2019
DOI: 10.1111/jfbc.13050
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effect of papaya ( Carica papaya ) pulp and seed extracts as a potential natural treatment for bacterial stress

Abstract: The current study evaluated the immunomodulatory effects of Carica papaya pulp and seeds methanol (MeOH) extracts on mice infected with Listeria monocytogenes. Gas chromatography–mass spectrometry analysis identified 10 active constituents in C. papaya seed MeOH extract and 10 compounds in C. papaya pulp MeOH extract. The experimental animals were divided into negative control (G1) group, positive control (G2) group, pulp extract treated (G3) group, and seed extract treated (G4) group. After infection of anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…The proinflammatory cytokines (IL‐10, IL‐12, IL‐1β, IL‐6, and TGF‐β1) were lower in the extract treated rats along with a decrease in levels of Nitric oxide. It was also noticed that the percentage of phagocytosis increased in extract treated mice (Amin et al., 2019).…”
Section: Immunity Booster Effects Of Various Fruitsmentioning
confidence: 94%
“…The proinflammatory cytokines (IL‐10, IL‐12, IL‐1β, IL‐6, and TGF‐β1) were lower in the extract treated rats along with a decrease in levels of Nitric oxide. It was also noticed that the percentage of phagocytosis increased in extract treated mice (Amin et al., 2019).…”
Section: Immunity Booster Effects Of Various Fruitsmentioning
confidence: 94%
“…Papaya leaf extract's immune modulatory potential is responsible for increasing the concentration of nitric oxide, CD80, TNF-alpha, and various other interleukins (IL-12p70, IL-12p40) and induction of apoptosis in cancer cells [ 37 , 69 ]. However, papaya leaf extract at concentrations of 5 Ig/mL on the release of cytokines exhibited percent inhibition of TNF- α (10.8%), IL-1 α (12.5%), IL-1 β (27.4%), IL-6 (42.9%), and IL-8 (8.4%) reported in some studies [ 80 ]. Possible mechanism of papaya leaf extract to act as an anticancerous agent is to lower down metastatic cancer by decreasing the extracellular matrix concentration which further acts as a chemo-attractants of PC-3 cells for adhesion as well as migration [ 76 ].…”
Section: Bioactivities Of Papaya Leaf Extractmentioning
confidence: 99%
“…There is a possibility that leaf extract of papaya may promote the control of Th2-mediated allergic ailment, or as an adjuvant of various vaccines by promoting an alteration from Th2 to Th1 type immune response [ 6 ]. The methanol (MeOH) extracts of C. papaya and on mice for 3 weeks were able to decrease the level of proinflammatory cytokine, and it was also found that use of standardized CPL aqueous extract (SCPLE) was significantly increasing the thrombocytes and phagocytic index in thrombocytopenic rats [ 80 ]. These findings help the researchers to screen out the anticancerous effects of papaya leaves on cancer cells in vivo studies.…”
Section: Bioactivities Of Papaya Leaf Extractmentioning
confidence: 99%
“…These compounds are 1,2-propanediol, 3-(octadecyloxy)-, diacetate; 2-trifluoroacetoxydodecane; 2-trifluoroacetoxypentadecane; 2-trifluoroacetoxytridecane; 3-eicosene, (E); and 4-hydroxy-4-methylhex-5-enoic. 1,2-propanediol, 3-(octadecyloxy)-, diacetate can also be found in African black pepper (Piper guineense) (Sulaimon et al 2020) and papaya (Carica papaya) pulp and seed (Amin et al 2019). They discussed the anti-inflammatory properties of these plants' extract.…”
Section: Resultsmentioning
confidence: 99%